Women’s Online Activism in Pakistan: Navigating Religious and Societal Constraints on Gender Identity - Jafri, Qamar Abbas; Rizwan, Muhammad (Indonesian Journal of Religion and Society, 2025)
This article analyses the disputed narratives regarding women's identity and public space in Pakistani society, as reflected in the ideological struggle between traditionalist and non-traditionalist power blocs. The primary objective of this research is to explore how group-based threat feelings shape the narrative and counter-narrative of gender rights, feminism, and religious identity in Pakistan. The study also aspires to analyze how the traditionalists perpetuate religious patriarchy, whereas non-traditionalists promote more political and social engagement of women. Based on Group Threat Theory as a conceptual lens, the study employs a qualitative case study methodology. It draws on social media data from Facebook, Twitter, and YouTube, complemented with newspaper, television, journal articles, and protest archives. Data were collected through thematic content analysis of social media, visual media, and grassroots activism, using search terms such as "Aurat March" and "anti-feminism Pakistan." The findings indicate an intense intergroup tension: women's rights organizations, civil society, and feminist foreign policy-supporting media voices, all non-traditionalists, believe women's liberty is under an existential threat due to entrenched religious patriarchy. They counter by demanding women's empowerment on such matters as body rights, marriage, dowry, and public participation. Alternatively, traditionalists view these demands as a cultural and symbolic threat to male authority, Islamic values, and morality. This results in militant counter-discourses, institutionalized resistance at the state level, and efforts to solidify conservative gender norms. The article finds that this intensifying group threat dynamic has grown into a bigger political and cultural conflict, setting gender identity politics in Pakistan but also across similarly structured postcolonial Muslim nations.